Communication theory and application in post-socialist contexts - Minielli, Maureen C.; Lukacovic, Marta N., 1985-; Samoilenko, Sergei A., 1976-; Finch, Michael R. (Communication, globalization, and cultural identity., 2022)
"Communication Theory and Application in Post-Socialist Contexts serves as a resource for anyone on the quest of diversifying and globalizing communication studies. It captures significant communication tendencies in several post-socialist countries and situates these tendencies within communication theory and application in a wide array of areas"--